Quality of life in patients with HTLV-I associated myelopathy/tropical spastic paraparesis Qualidade de vida em pacientes com mielopatia associada ao HTLV-I/paraparesia espástica tropical - José Vicente Pereira Martins; Abrahão Fontes Baptista; Abelardo de Queiroz Campos Araújo (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To assess the quality of life (QoL) of patients with HTLV-I-associate myelopathy/tropical spastic paraparesis (HAM/TSP) and to correlate it with specific aspects of the disease. METHODS: Fifty-seven HAM/TSP patients completed the SF-36 QoL questionnaire. They were also asked about common complaints related to the disease, and we looked for associations between QoL and these complaints. RESULTS: Patients with HAM/TSP showed a strong negative association to QoL. Pain was the condition which most affected their QoL. The practice of physical activity is associated with better QoL in five out of eight domains of the scale. CONCLUSION: HAM/TSP leads to a poor QoL, mostly influenced by pain. Physical activity may have a positive association to QoL of these patients. OBJETIVO: Avaliar a qualidade de vida (QV) em pacientes com mielopatia associada ao HTLV-I/paraparesia espástica tropical (MAH/PET) e correlacioná-la com aspectos específicos da doença. MÉTODOS: Cinquenta e sete pacientes com MAH/PET completaram o questionário de qualidade de vida SF-36. Também foram feitas perguntas sobre queixas comuns relacionadas à doença e investigadas posteriormente associações entre QV e essas queixas. RESULTADOS: Pacientes com MAH/PET apresentaram uma associação negativa com a QV. A dor foi a condição que mais afetou a QV. A prática de atividade física foi associada a uma melhor QV em cinco dos oito domínios da escala. CONCLUSÃO: MAH/PET leva a uma pior QV, principalmente influenciada pela dor. A atividade física pode estar positivamente associada à QV destes pacientes.